Odpowiedzi

2009-11-20T15:46:50+01:00
(x³ - 6x² + 11x - 6) : (x² - 5x + 6) = x -1

[4 /(x - 2)] - [5 /(x + 2)] = 20 / (x² - 4)
[4 × (x + 2) - 5 × (x - 2)] /(x - 2)(x + 2) = 20 / (x² - 4) / × (x²-4)
4x + 8 - 5x + 10 = 20
-x = 2
x = -2

(x² + 7x + 12) / (x² - 1) > 0
D = R \ {-1; 1}
(x² + 7x + 12)(x² - 1) / (x² -1)(x² - 1) > 0
(x² + 7x + 12)(x - 1)(x + 1) > 0
x₁ = -4
x₂ = -3
x₃ = 1 x₃ ∉ D
x₄ = -1 x₄ ∉ D
x∈( - ∞; -4) i (-3; -1)
1 1 1
Najlepsza Odpowiedź!
2009-11-20T16:28:21+01:00
1)x³-6x²+11x-6/(x²-5x+6)=x-1
-x³+5x²-6x
___________
= -x²+5x-6
x²-5x+6
____________
= = =
To jest kompletne dzielenie wielomianów
2)4/x-2-5/x+2=20/x²-4
4*(x+2)-5(x-2)/x²-4=20/x²-4
4x+8-5x+10/x²-4=20/x²-4
-x+18/x²-4-20/x²-4=0
-x-2/x²-4=0
(-x-2)(x²-4)=0
pierwiastek podwójny→(x=-2)∨x=2
3)x²+7x+12/x²-1>0
(x²+7x+12)(x²-1)>0
Δ=7²-4*1*12 x²=1
=49-48=1 x₃=1∨x₄=-1
pierw.zΔ=1
x₁=-7-1/2=-4
x₂=-7+1/2=-3
x∈(-4;-3)∨(-1;1)
1 1 1
2009-11-20T19:38:17+01:00